MEWUJUDKAN EKONOMI ISLAM DENGAN RUH AL-âADL (Studi Pada YaPEIM Malaysi) (IAIN Tulungagung, 2015)
Islamic Economics is a discipline is studying the behavior of human economic behavior are arranged based on the religion of Islam and tawheed with as it is based in the tenets of the faith and the tenets of Islam. All the rules that lowered the Almighty God in the Islamic sistem leads to the achievement of goodness, welfare, priority, as well as abolish evil, suffering and loss on the whole of his creation. Likewise with the economy, the goal is help humans achieve victory in the world and the hereafter. YaPEIM (Foundation of economic development Islam Malaysia) is one of the institutions that fght for the introduction of Islamic Economy concentrated in Malaysia. Embody the spirit of AL-â ADL in the economy became the spirit of struggle of YaPEIM. This research is a Case Study in YaPEIM in Changloon, Kedah, Malaysia. This case Study presents what goals, decision-making, and economic activity from YaPEIM in establishing and developing the economy of Islam with the spirit of al-âadl.Keywords: Economics, Islam, al-âadl, YaPEIM